Ultra high temperature latent heat energy storage and thermophotovoltaic energy conversion. (15th July 2016) - Datas, Alejandro; Ramos, Alba; Martí, Antonio; del Cañizo, Carlos; Luque, Antonio
Abstract: A conceptual energy storage system design that utilizes ultra high temperature phase change materials is presented. In this system, the energy is stored in the form of latent heat and converted to electricity upon demand by TPV (thermophotovoltaic) cells. Silicon is considered in this study as PCM (phase change material) due to its extremely high latent heat (1800 J/g or 500 Wh/kg), melting point (1410 °C), thermal conductivity (∼25 W/mK), low cost (less than 2/kg or 4/kWh) and abundance on earth. The proposed system enables an enormous thermal energy storage density of ∼1 MWh/m 3, which is 10–20 times higher than that of lead-acid batteries, 2–6 times than that of Li-ion batteries and 5–10 times than that of the current state of the art LHTES systems utilized in CSP (concentrated solar power) applications. The discharge efficiency of the system is ultimately determined by the TPV converter, which theoretically can exceed 50%. However, realistic discharge efficiencies utilizing single junction TPV cells are in the range of 20–45%, depending on the semiconductor bandgap and quality, and the photon recycling efficiency. This concept has the potential to achieve output electric energy densities in the range of 200–450 kWhe /m 3, which is comparable to the best performing state of the art Lithium-ion batteries. Highlights: We model a novel conceptual system for ultra high temperature energy storage. Operation temperature exceed 1400 °C, which is the silicon melting point. Extremely high thermal energy densities of 1 MWh/m 3 are attainable. Electric energy densities in the range of 200–450 kWh/m 3 are attainable. The system can be used for both solar and electric energy storage.